Chandigarh revealed Le Corbusier's city today - Fynn, Shaun (Princeton Architectural Press, 2017)
"In 1950, Indian prime minister Jawaharlal Nehru invited legendary French-Swiss architect Le Corbusier to embark on one of the greatest experiments in urban planning history: to build on the flat plains of Punjab a new capital...Chandigarh, a city whose monumental modernism promised to free India from the fetters of colonial tradition and lay the groundwork for an independent and utopian future. Nicknamed the City Beautiful, Chandigarh has been called one of "the perfect cities of the world in terms of architecture, cultural growth, and modernization," and in 2016 was designated a UNESCO World Heritage Site. Six decades after its founding, photographer and Chandigarh resident Shaun Fynn was granted unprecedented access to turn his lens on Le Corbusier's city and capture what is rarely seen: the living metropolis behind the master plan. Fynn's captivating images of the city and its inhabitants observe how the poetry of the architect's compositions have been shaped by the tumult of everyday life and worn by the forces of time. Chandigarh Revealed combines striking photographs, texts by Le Corbusier authorities, an interview with one of the last remaining architects from Le Corbusier's team, and custom-designed maps to create an astonishing and intimate portrait of a legendary city"...